Simulated Interannual Modulation of Intraseasonal Kelvin Waves in the Equatorial Indian Ocean - Iskhaq Iskandar; Dedi Setiabudidaya; Wijaya Mardiansyah; Muhammad Irfan (Institute for Research and Community Services (LPPM) ITB, 2016)
Outputs from a high-resolution ocean general circulation model (OGCM) for the period of 1990-2003 indicate an interannual modulation of intraseasonal Kelvin waves along the equatorial Indian Ocean. During normal conditions without IOD event, the first mode explains about 30-40% of the total variance in the western (60-65ºE) and central (75-80ºE) basin, while the second mode contributes up to 45% to the total variance in the central basin around the longitude of 82ºE. In contrast, during the 1997/98 IOD event, the fourth mode caused about 40% of the total variance in the central and eastern basin. During the 1994 IOD event, the contribution from the fourth baroclinic mode in the eastern basin caused 45% of the total variance. In the central basin, the second and the fourth baroclinic mode caused almost the same variance ( 40%). The variations in the characteristics of the intraseasonal Kelvin waves are related to variations in the vertical stratification. During the IOD event, the pycnocline in the eastern basin was raised by about 50 m and the stratification at the upper level is strengthened, while it is weakened at lower levels. These changes lead to an increase in the contribution of higher-order baroclinic modes.